Tingkat Pengetahuan antara Mahasiswa Kesehatan dan Non Kesehatan terhadap Penggunaan Vitamin C di Universitas Tadulako Sulawesi Tengah - Siti Mutmaina Ayu Lestari; Amelia Rumi; Khusnul Diana (Jurnal Health Sains, 2021)
During the Covid-19 pandemic, it is recommended to use vitamin C in maintaining immunity, especially in students who have high activity. Widespread use can lead to dose abuse, resulting in side effects such as diarrhea, vomiting nausea to the formation of kidney stones. The purpose of this study was to determine the knowledge and use of vitamin C as well as the relationship between both medical and non-medical students of Tadulako University. This study used cross sectional method by collecting data through questionnaires in Google Form in 747 medical and non-medical students in the class of 2017-2019. Sampling techniques using purposive sampling. The results of the study obtained the knowledge of tadulako university medical students about vitamin C entered the sufficient category (47.01%) and non-medical students were included in the low category (59.01%). For the use of vitamin C, medical students fall into the high category (61.54%) and non-medical students were included in the sufficient category (48.74%). The results of the chi-square test, there is a significant relationship between knowledge and the use of vitamin C, with p value 0.000 (p value <0.05). The conclusion from the research, the knowledge of medical students about vitamin C and its use is better than non-medical students, and there is a link between the knowledge and use of vitamin C in tadulako university students.